Comparison of pain and postoperative stress in dogs undergoing natural orifice transluminal endoscopic surgery, laparoscopic, and open oophorectomy - Freeman, Lynetta J.; Rahmani, Emad Y.; Al-Haddad, Mohammad; Sherman, Stuart; Chiorean, Michael V.; Selzer, Don J.; Snyder, Paul W.; Constable, Peter D. (Gastrointestinal endoscopy, 2010)
Few studies are available to compare the potential benefits of natural orifice transluminal endoscopic surgery (NOTES) approaches to traditional surgery. To compare complications, surgical stress, and postoperative pain. Prospective study in dogs. Research laboratory. Thirty dogs. Oophorectomy procedures were performed via NOTES and laparoscopic and traditional open surgery. Operative time, pain scores, systemic stress parameters (cortisol, glucose), surgical stress markers (interleukin 6, C-reactive protein), 3-day observation. Median operative times were 76, 44, and 35 minutes for the NOTES, laparoscopic, and open procedures, respectively, with the NOTES procedure being significantly longer than the other 2 procedures. All ovaries were completely excised, and all the animals survived without complications. The NOTES animals had greater increases in serum cortisol concentrations at 2 hours but no statistically significant differences in glucose concentrations compared with the other groups. Serum interleukin 6 and C-reactive protein concentrations were significantly increased at specific times compared with baseline in the NOTES group, but not in the open or laparoscopic surgery groups. Based on the cumulative pain score and nociceptive thresholds, the animals in the NOTES group demonstrated less evidence of pain. Small sample size, limited follow-up. Although the NOTES oophorectomy procedures took approximately twice as long and there may be more evidence of tissue damage as judged by increases in serum cortisol and interleukin 6 concentrations, the dogs in the NOTES group had lower pain scores, especially when compared with animals undergoing open surgery.